2012
DOI: 10.1177/0038038512453789
|View full text |Cite
|
Sign up to set email alerts
|

Middle-class Mothers’ Moralities and ‘Concerted Cultivation’: Class Others, Ambivalence and Excess

Abstract: Drawing on a small qualitative study of mothers in the UK, this article argues that although concerted cultivation and intensive parenting are legitimated as 'good' parenting, these discourses have uneven effects on middle-class mothers' moral identities. My contention is that by focusing too much on processes of capital accumulation and transmission, studies of parenting risk simplifying the contradictory effects of these discourses on middle-class parents' subjectivities. I argue that accounting for how powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 32 publications
2
58
1
4
Order By: Relevance
“…Karen indicates that in disallowing their identity to be subsumed by motherhood women may be perceived as 'not caring', and, by implication, as being a 'bad mother', thus revealing something about the difficulties associated with managing these two competing positions: the self, and the 'good' intensive middle-class mother. These findings are similar to those of Perrier (2012) who found that middle class mothers seemed caught between resisting and complying with the demands of intensive motherhood.…”
Section: Challenging Intensive Motherhood Approaches To Infant Develosupporting
confidence: 89%
“…Karen indicates that in disallowing their identity to be subsumed by motherhood women may be perceived as 'not caring', and, by implication, as being a 'bad mother', thus revealing something about the difficulties associated with managing these two competing positions: the self, and the 'good' intensive middle-class mother. These findings are similar to those of Perrier (2012) who found that middle class mothers seemed caught between resisting and complying with the demands of intensive motherhood.…”
Section: Challenging Intensive Motherhood Approaches To Infant Develosupporting
confidence: 89%
“…The contradictions and anxieties experienced by Kaisa and Mika and their parents also foreground emotional aspects and the heterogeneity of middle‐class families. These anxieties echo findings by Perrier () and Reay (, ) in which what middle‐class mothers saw as beneficial for their children from an educational viewpoint was not free of ethical conflicts, exemplified, for example, in anger over their children's lack of interest in schoolwork or in critical and contradictory attitudes towards the formal learning of small children. In this study, the ethical conflicts faced by children and parents were feelings of pressure and stress over workload and the conflict between having peer‐related problems in school versus the future civic competencies and advantages held out to TCP office holders.…”
Section: Synthesis: Parental Strategies and Emotional Contradictionssupporting
confidence: 65%
“…However, applying the ideas of social reproduction presents a risk of understanding middle‐class parents solely as capital‐bearing and transmitting individuals (Perrier, , p. 658). Cultural capital is not a static resource linked only to class differentials nor does it work only to secure class privileges.…”
Section: Middle‐class Families Cultural Resources and Emotionsmentioning
confidence: 99%
“…Instead, we explored how participants themselves used 'class', perceptually and linguistically (Atkinson, 2010, p. 161) to account for their school choice. This allows for the emergence of 'class talk' as participants attempt to make sense of their decisions and how they implicitly position themselves and others within the classed hierarchy (Atkinson, 2010;Perrier, 2012). It is in such accounts that class experiences are revealed (Savage, 2000) as participants offer observations and evaluations of the social environment of the school from the interpretive standpoint of their class positions.…”
Section: Methodsmentioning
confidence: 99%